SOSIALISASI PENCEGAHAN STUNTING MELALUI PELATIHAN PEMBUATAN ANEKA MAKANAN SEHAT BERBASIS REMUNGGAI DI KELURAHAN SIDOMULYO KOTA BENGKULU - Ikhsan Hasibuan; Prihanani Prihanani (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Stunting is now identified as a major world health priority. Of the world’s 161 million stunted children, about half lived in Asia. Moreover, Bengkulu province is known as a stunting locus in Indonesia with 26.86% of children being classified as stunted. People’s knowledge is one of the main factors that influence stunting growth. Thus, giving information about stunting is an important activity that needs to be done in terms of its prevention. This activity aimed to share information about stunting and how to prevent it by utilizing moringa, and demonstrate how to cook moringa to become healthy and delicious food. The process of this program was socializing about stunting and moringa, and demonstrating cooking moringa into some food and drink. The methods applied were giving a speech, discussion, demonstration, and participant participatory. The main results of these service activities were increasing participant knowledge about stunting and how to prevent it by using moringa for about 88% and 85%, respectively. Ninety-five percent of participants have had the ability to cook moringa into healthy and delicious food. Likewise, those participants are willing to include moringa in the daily menu. Finally, based on these results we believe that what have we done could reduce the number of stunting especially in the Sidomulyo urban village, Bengkulu City